(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines the category of advice in advertising texts written in Uzbek and English, paying particular attention to linguistic, rhetorical, and cultural factors. An examination of advertising materials in comparison shows that both languages offer advice through the use of imperatives, modal verbs, and rhetorical questions. Both languages make use of authority, social proof, and emotional appeals in their rhetoric. But there are cultural variations as well. Uzbek society likes more nuanced discourse, whereas English-speaking cultures are typically more open to direct instruction. The practical ramifications of these findings for advertisers looking to develop successful campaigns in a variety of markets are noteworthy.